The dilemma of non-agency vs. provocativeness in victimhood accounts of young people - Karagianni, Kyriaki; Sapountzis, Antonis (Psychology: the Journal of the Hellenic Psychological Society, 2023)
Psychological theory and research on school violence and bullying have interlinked the victim’s profile to vulnerability and irresponsiveness, without alternative constructions of victim’s identity being discussed. This strand of research approaches victims as members of low-status groups, and thus as statedly holding a less dominant position among their peers. While social-psychological research drawing on social identity approach has argued that young people who are victimized are likely to build up on a common identity, the present paper discusses how young people in their everyday interactions may be distanced from the nonagentic identity of victim. The purpose of the present study is to analyze how the victim’s identity is constructed in young people’s interactions regarding bullying and violence. To analyze the data, concepts/tools drawing on discursive psychology and rhetorical psychology are used. Victimhood dilemmas arose in lay interaction, with the main concern of young people being not to be self-positioned as victims. The victim’s identity was often related to a lack of agency or even to slight provocativeness. While the perpetrators were very often constructed as irrationally aggressive people, in other cases, the participants were mainly referred to the victim’s provocativeness or excessive passivity to justify the persistence of victimizing acts.